Bulk Etch Rate of CR-39 Detector Using NaOH/Ethanol Etchant - Y. Y. Kasim (Jordan Journal of Physics, 2025)
Extended Abstract: The science of solid-state nuclear track detectors was born in 1958.Operation of the solid-state nuclear track detector is based on the fact that a heavy charged particle will cause extensive ionization of the material when it passes through a medium. The bulk etch rate VB is the rate of removal of the undamaged surface of the detector. Due to the chemical reaction between the etching solution (etchant) and the detector material, some molecules of the detector material are removed. The final effect is the removal of the material from the detector surface. During etching, the material is removed layer by layer and the thickness of the detector becomes smaller and smaller. The aqueous solutions of NaOH or KOH are the most frequently used chemical solutions in this regard. . . . Keywords: SSNTD's, Bulk etch rate, CR-39, Ethanol etchant.